Grading of gliomas using 3D CEST imaging with compressed sensing and sensitivity encoding. Issue 158 (January 2023) - Wada, Tatsuhiro; Togao, Osamu; Tokunaga, Chiaki; Oga, Masahiro; Kikuchi, Kazufumi; Yamashita, Koji; Yamamoto, Hidetaka; Yoneyama, Masami; Kobayashi, Koji; Kato, Toyoyuki; Ishigami, Kousei; Yabuuchi, Hidetake
Highlights: Three-dimensional CEST imaging has the equivalent diagnostic performance as two-dimensional CEST imaging. Multi-slice CEST imaging is able to describe the variation of signal intensity in each imaging section. Key images can be selected from multi-slice CEST imaging. Abstract: Purpose: We evaluated the usefulness of three-dimensional (3D) chemical exchange saturation transfer (CEST) imaging with compressed sensing and sensitivity encoding (CS-SENSE) for differentiating low-grade gliomas (LGGs) from high-grade gliomas (HGGs). Methods: We evaluated 28 patients (mean age 51.0 ± 13.9 years, 13 males, 15 females) including 12 with LGGs and 16 with HGGs, all acquired using a 3 T magnetic resonance (MR) scanner. Nine slices were acquired for 3D CEST imaging, and one slice was acquired for two-dimensional (2D) CEST imaging. Two radiological technologists each drew a region of interest (ROI) surrounding the high-signal-intensity area(s) on the fluid-attenuated inversion recovery image of each patient. We compared the magnetization transfer ratio asymmetry (MTRasym) at 3.5 ppm in the tumors among the ( i ) single-slice 2D CEST imaging ("2D"), ( ii ) all tumor slices of the 3D CEST imaging (3Dall ), and ( iii ) a representative tumor slice of 3D CEST imaging (maximum signal intensity [3Dmax ]). The relationship between the MTRasym at 3.5 ppm values measured by these three methods and the Ki-67 labeling index (LI) of the tumors was assessed. Diagnostic performance was evaluated with a receiver operating characteristic analysis. The Ki-67LI and MTRasym at 3.5 ppm values were compared between the LGGs and HGGs. Results: A moderate positive correlation between the MTRasym at 3.5 ppm and the Ki-67LI was observed with all three methods. All methods proved a significantly larger MTRasym at 3.5 ppm for the HGGs compared to the LGGs. All methods showed equivalent diagnostic performance. The signal intensity varied depending on the slice position in each case. Conclusions: The 3D CEST imaging provided the MTRasym at 3.5 ppm for each slice cross-section; its diagnostic performance was also equivalent to that of 2D CEST imaging.